INTELLIGENT CONTROL SYSTEM OF A WHEELCHAIR FOR PEOPLE WITH QUADRIPLEGIA PARALYSIS - Fadhil, hayder; Hussam, Saif; Sadoon, Yasseen (IIUM Engineering Journal, 2019)
Our system proposes a wheelchair controlled by head gestures for people with quadriplegia paralysis (QP) or for those suffering from amputation of their hands and legs during the war in Iraq. The wheelchair design has an intelligent control that works with the movement of a patient‘s head in order to enable the patient to drive the wheelchair in the desired direction. The system consists of two main parts. The first is the transmitter in which sensing signals are transmitted to the second part and it consists of a 3-axes accelerometer (ADXL-345), a 433 MHz RF wireless receiver transmitter module, and Arduino UNO. The ADXL-345 sensor is placed in front of a hat that the patient wears. The system detects the direction of the patient's head movement then sends appropriate instructions to the wheelchair’s control part (receiving part). The receiving part is the wheelchair control system that consists of a 433 MHz RF wireless receiver transmitter module and an Arduino UNO. The Arduino processes the signals coming from the first part and moves the wheelchair accordingly in the desired direction. The research also provides an obstacle avoidance system with a range of 50 cm that prevents the wheelchair from colliding with objects. The head movement angles have been selected to be 40, 35 degree for vertical and horizontal movement respectively so that the QP patient feels comfortable to tilt his head in all directions and control the wheelchair easily. The system provides a very effective performance and accuracy. ABSTRAK: Sistem ini bergantung kepada kerusi roda yang dikawal menggunakan isyarat kepala untuk mereka yang lumpuh kuadriplegia (QP) ataupun mereka yang dipotong tangan dan kaki semasa perang di Iraq. Ia merupakan reka bentuk pintar pada kerusi roda dan pesakit boleh mengawal pergerakan mereka dengan isyarat pada kepala. Sistem ini terdiri daripada dua bahagian utama iaitu yang pertama merupakan pemancar yang menghantar isyarat gerakan ke bahagian kedua dan ianya terdiri daripada 3 axis accelerometer (ADXL-345), modul penerima isyarat pemancar tanpa wayar 433 MHz RF dan Arduino UNO. Sensor ADXL-345 ini diletakkan di bahagian depan topi yang dipakai oleh pesakit. Sistem ini mengesan arah gerakan kepala pesakit dan kemudiannya arahan dihantar ke bahagian pengendali kerusi roda (bahagian penerimaan isyarat). Bahagian ini merupakan sistem pengendalian kerusi roda yang terdiri daripada modul pemancar penerimaan tanpa wayar 433 MHz RF dan Arduino UNO. Arduino memproses isyarat yang datang dari bahagian pertama bagi menggerakkan kerusi roda ke arah yang dikehendaki. Kajian ini turut menyediakan sistem mengelak halangan pada jarak 50 cm bagi menjauhi kerusi roda daripada melanggar objek. Sudut gerakan kepala telah dipilih pada 40, 35 darjah bagi gerakan menegak dan mendatar masing-masing, supaya pesakit QP merasa selesa bagi mengerakkan kepalanya ke semua arah dan mengawal kerusi roda dengan mudah. Sistem ini juga sangat cekap dan tepat dalam mengawal arah.